PRLR-AluI Gene Polymorphism And Litter Size Traits In Highly Prolific Line Of Topigs 20 Sows - Menčik Sven (Sciendo, 2015)
The objective of the present study was to identify the Prolactin Receptor (PRLR) gene polymorphism related to litter size traits. The study included 101 Topigs 20 line of sows with 426 litters. The traits studied were: Total Number of Born (TNB), Number of Born Alive (NBA), Number of Still Born (NSB), and Number of MUMmified (NMUM) piglets. Polymorphism was identified with the polymerase chain reaction-restriction fragment length polymorphism method. Allelic and genotype frequencies and deviation from Hardy-Weinberg equilibrium were verified with the chi-square test. Analysis of litter size traits was performed using the General Linear Model, which included the potential environmental effects. Additive and dominant allele variances were observed by the regression procedure. In the studied population of sows, the frequency of heterozygotes (0.5149) for PRLR gene exceeded the total number of AA (0.0198) and BB (0.4653) homozygotes, which resulted in a high proportion of B allele (0.7228). The results for PRLR showed statistically significant (P<0.05) differences in first parity sows between BB and AB genotypes for TNB and NBA. Significant differences (P<0.05) were recorded in third parity sows between BB and AB genotypes for NBA, and in AA genotype versus AB and BB genotypes for NMUM. The fourth and subsequent parity sows of AA genotype had a significantly higher (P<0.05) rate of NBA as compared with those of AB and BB genotypes. In all parities analysed, the difference between the BB and AB genotypes for NBA was statistically significant (P<0.05). Interpretation of the results at the levels of phenotypes and either additive or dominant variance was quite difficult due to the small number of AA homozygous sows. The calculation model yielded a significant effect (P<0.05) as well as tendency (P<0.1) for the mentioned effects except for age at first farrowing.